Modification of malachite surfaces with lead ions and its contribution to the sulfidization flotation - Wang, Han; Wen, Shuming; Han, Guang; Feng, Qicheng (Applied surface science, 2021)
[Display omitted] •Lead ions can adsorb onto malachite surfaces and form Pb-O species.•Pb-S species formed on malachite surfaces, and Cu(II) were reduced to Cu(I).•S species increased on malachite surfaces after treatment with lead ions.•Lead ions positively affected the flotation recovery of malachite. Malachite is a common copper-oxide resource, and it is usually enriched by sulfidization flotation. Its floatability and recovery are greatly determined by the surface sulfidization results. In this paper, Pb(NO3)2 is used to pretreat malachite, and the sulfidization mechanism of malachite was studied through microflotation experiments, zeta-potential determination, adsorption tests, XPS and ToF-SIMS. The flotation and adsorption results show that the malachite floatability after pretreatment with Pb ions improved significantly. Compared with Na2S treatment, the maximum recovery increased by 42.6% after treatment with lead ions and Na2S. The zeta potential results showed that lead ions (such as Pb(OH)+) could adsorb on the malachite surface, and the surface active sites of malachite were increased. XPS results indicate that lead ions adsorbed onto the mineral surface through the interaction between Pb species, S species and O species. The formation for new species (such as Pb-S) enhanced the malachite sulfidization. ToF-SIMS was used to visualize the three-dimensional distribution of lead- and sulfur-species adsorbed on the malachite surface. It demonstrated that the sulfidization layer increased after pretreatment with Pb(NO3)2, facilitating the surface hydrophobicity and flotation recovery of malachite.